Pengaruh Waktu Fermentasi terhadap Karakteristik Minuman Tepache Gula Kelapa - Jihan Salsa Olii; A. Nurfitriani; Satriawati Pade; Tri Handayani; Asriani Laboko; Asniwati Zainuddin; Ika Okhtora Angelia (Program Studi Teknologi Hasil Pertanian Fakultas Sains dan Teknologi Hasil Pertanian Universitas Muhammadiyah Sidenreng Rappang, 2026)
Honey pineapple peel, which is often underutilised and becomes a source of waste, contains secondary metabolites. The aim of this study was to determine the effect of varying fermentation times on the chemical and organoleptic analysis of tepache made from honey pineapple peel (Ananas comosus L. merr). The parameters observed included pH analysis, alcohol content, and organoleptic testing. Statistical validity of the results and analysis of variance (ANOVA) were used to determine the significance of differences between fermentation time treatments. Data collection employed a completely randomised design (CRD) with three fermentation time treatments (1 day, 3 days and 5 days). The results of the study showed that fermentation time had a significant effect on the chemical and organoleptic properties of tepache made from honey pineapple peel with coconut sugar. The lowest pH was achieved on day 5 (W3) (4.41), with an alcohol content of 0.06%. Meanwhile, the results of the organoleptic test showed that fermentation for 3 days (W2) was preferred by the panelists based on assessments of taste, aroma, colour, and overall quality. Thus, the best minimum fermentation time from the results of this study was on the third day and the optimal time was on the fifth day. Keywords: Fermentation, Coconut sugar, Tepache